Gamma-glutamyltransferase activity as a surrogate biomarker of metabolic health status in young nondiabetic obese women. (May 2017) - Mankowska-Cyl, Aneta; Krintus, Magdalena; Rajewski, Pawel; Sypniewska, Grazyna
Aim: We investigated the association of gamma-glutamyltransferase (GGT) activity with atherogenic risk factors and metabolic health status in young nondiabetic obese women.Methods & results: In 140 obese women GGT activity was independently associated with BMI, triglyceride to high-density cholesterol ratio and homeostasis model assessment. Metabolically healthy but obese women had significantly lower GGT activity, associated with a normal insulin sensitivity, favorable lipid profile and apolipoprotein B to apolipoprotein AI ratio. GGT activity showed good diagnostic accuracy to distinguish between metabolically healthy but obese and obese women at risk (77.8% sensitivity and 60% specificity). GGT activity >17 U/l can predict atherogenic risk and insulin resistance.Conclusion: GGT activity may serve as a potential surrogate biomarker of atherogenic risk and metabolic health status.